Hematocrit and lactate trends help predict outcomes in trauma independent of CT and other clinical parameters - Staziaki, Pedro V.; Qureshi, Muhammad M.; Maybury, Aaron; Gangasani, Neha R.; LeBedis, Christina A.; Mercier, Gustavo A.; Anderson, Stephan W. (Frontiers in Radiology, 2023)
Background: Hematocrit and lactate have an established role in trauma as indicators of bleeding and cell death, respectively. The wide availability of CT imaging and clinical data poses the question of how these can be used in combination to predict outcomes.To assess the utility of hematocrit or lactate trends in predicting intensive care unit (ICU) admission and hospital length of stay (LOS) in patients with torso trauma combined with clinical parameters and injury findings on CT.This was a single-center retrospective study of adults with torso trauma in one year. Trends were defined as a unit change per hour. CT findings and clinical parameters were explanatory variables. Outcomes were ICU admission and hospital LOS. Multivariate logistic and negative binomial regression models were used to calculate the odds ratio (OR) and incident rate ratio (IRR).Results: Among 840 patients, 561 (72% males, age 39 ± 18) were included, and 168 patients (30%) were admitted to the ICU. Decreasing hematocrit trend .58], p=0.002) and increasing lactate trend .01], p=0.012) were associated with increased odds of ICU admission. LOS median was 2 (IQR: 1-5) days. Decreasing hematocrit trend ], p= 0.002) and increasing lactate trend (2.02 [1.43-2.85], p < 0.001) were associated with longer hospital LOS.Hematocrit and lactate trends may be helpful in predicting ICU admission and LOS in torso trauma independent of organ injuries on CT, age, or admission clinical parameters.